2015
DOI: 10.4278/ajhp.130514-qual-247
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Recruitment Barriers, Motivators, and Community-Based Strategies for Increasing Clinical Trials Participation among Rural and Urban Populations

Abstract: Perceived recruitment barriers, motivators, and strategies did not differ considerably between rural and urban groups. Major barriers identified by participants should be addressed in future CT recruitment and education efforts. Findings can inform recruitment and communication strategies for reaching both urban and rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 40 publications
6
77
1
Order By: Relevance
“…However, in the context of consent to participate in research, a previous systematic review that found no difference in consent rates between minority--African Americans, Hispanics-- and non-Hispanic whites [51]. While we did not find health status to be a predictor, other studies have found that patients with poorer health are more likely to consent to a research study [52, 53]. …”
Section: Discussioncontrasting
confidence: 83%
“…However, in the context of consent to participate in research, a previous systematic review that found no difference in consent rates between minority--African Americans, Hispanics-- and non-Hispanic whites [51]. While we did not find health status to be a predictor, other studies have found that patients with poorer health are more likely to consent to a research study [52, 53]. …”
Section: Discussioncontrasting
confidence: 83%
“…5 Key issues that may detrimentally affect rural residents' participation in research include cultural sensitivity, geographic challenges (e.g., distance and isolation), misperceptions of research, and lack of opportunities to participate in research. [6][7][8] Furthermore, prior research suggests that participation in health research is disproportionate across races and ethnicities. While racial/ethnic minorities constitute a third of the US population, most published studies show that they remain largely underrepresented in health research.…”
mentioning
confidence: 99%
“…We employed a mixed methods approach using focus groups [1,12] and a telephone survey [2,3]. First we conducted 19 focus groups and eight interviews statewide with a total of 212 participants.…”
Section: Phase Ii: We Assessed Adults' Current Ct Knowledge and Beliementioning
confidence: 99%